ANALYZING THE FACTORS THAT AFFECT THE FINANCIAL REPORTING TIMELINESS OF MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Mulia Saputra; Indayani Indayani; Wilsen Yungata (Universitas Padjadjaran, 2020)
This study aims to find the empirical evidence about the factors that affect the timeliness of financial reporting in companies listed on the Indonesian Stock Exchange. The factors tested in this study are tax avoidance, audit opinion, and leverage ratio. The samples consist of 100 manufacturing companies listed on the Indonesian Stock Exchange from 2014-2017. The 400 total observed cases are comprised of annual reports from the selected companies are analyzed using logistic regression. The results of this study identified that audit opinion affects the timeliness of financial reporting, while tax avoidance and leverage have no effect on the timeliness of financial reporting of companies listed on the Indonesian Stock Exchange.